2022
DOI: 10.1111/acer.14946
|View full text |Cite
|
Sign up to set email alerts
|

The role of alcohol and cannabis co‐use in drinking rate and its impact on consequences

Abstract: Background The impact of alcohol and cannabis co‐use on college student drinking and related outcomes is complex. Specific characteristics or patterns of co‐use events beyond drinking quantity may be important to the experience of consequences. The present study used repeated daily surveys to examine the association between co‐use (versus use of alcohol only) and drinking rate on negative consequences. Methods The sample included 318 college students (Mage = 19.8, 47% female, 76% non‐Hispanic White) who were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
7
1
Order By: Relevance
“…These findings are similar to the results of two previous studies that examined how cannabis use moderates the day‐level association between indices of alcohol consumption (i.e., number of drinks, rate of consumption) and negative alcohol consequences, which found that cannabis use (vs. no use) weakened this within‐person association (Gunn et al., 2022; Sokolovsky et al., 2020). However, the nature of the moderating effect we observed differed from these prior studies when comparing the simple slopes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These findings are similar to the results of two previous studies that examined how cannabis use moderates the day‐level association between indices of alcohol consumption (i.e., number of drinks, rate of consumption) and negative alcohol consequences, which found that cannabis use (vs. no use) weakened this within‐person association (Gunn et al., 2022; Sokolovsky et al., 2020). However, the nature of the moderating effect we observed differed from these prior studies when comparing the simple slopes.…”
Section: Discussionsupporting
confidence: 89%
“…This might reflect the tendency for heavy drinking to be risky in general, and so adding cannabis to a heavy drinking episode may not confer much additional risk; in contrast, the addition of cannabis to a light drinking episode may escalate intoxication to levels that confer greater risk for harms than would be expected from light drinking alone. However, contrary to the findings of Boyle et al, other ILD studies have found that the quantity of alcohol consumed (Sokolovsky et al, 2020) and rate of alcohol consumption (Gunn et al, 2022) were weaker predictors of negative consequences on simultaneous use days relative to alcohol-only days. This suggests that perhaps cannabis can have quantities.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In our study, HID days were associated with the quickest pace of drinking, as well as a greater number of consequences. Other work also highlights the relationship between quicker rates of drinking and negative alcohol consequences, even when controlling for quantity of drinks consumed (Carpenter & Merrill, 2021; Gunn et al, 2022; Kuntsche et al, 2015). Although our measurement of HID is focused on the number of drinks consumed, it still evidenced the fastest pace and greatest number of consequences compared with other drinking levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Carpenter and Merrill (2021) found that the amount of alcohol consumed and the rate of consumption were both associated with a greater likelihood of experiencing a negative consequence (e.g., blackout and hangover) the next morning. Finally, Gunn et al (2022) found that both consuming more drinks during the peak hour of drinking and faster daily rate of drinking were associated with experiencing negative consequences, even when controlling for the amount of alcohol consumed. Taken together, these findings suggest that accounting for the rate of drinking is important when assessing risk for negative alcohol consequences.…”
Section: Introductionmentioning
confidence: 99%